2006
DOI: 10.1021/tx600270f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Nature of Stochastic Generation of Protein-based Carbonyls:  Metal-catalyzed Oxidation versus Modification by Products of Lipid Oxidation

Abstract: An assessment of 2,4-dinitrophenylhydrazine (DNPH)-detectable protein-based carbonyls is one of the most common assays used to quantify oxidative stress in vitro and in vivo. In this study, we compared, for the lipid-binding protein beta-lactoglobulin, the extent to which carbonyl reactivity could be introduced by adventitious metal-catalyzed oxidation (MCO) in the absence and presence of a polyunsaturated lipid or by treatment with various individual bifunctional lipid oxidation products capable of introducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 63 publications
(75 reference statements)
2
39
0
4
Order By: Relevance
“…Methods are in development to isolate and analyze such alkylated peptides to determine the site(s) and stoichiometry of carbonylation. Additionally, although both amino acid side chain oxidation and carbonylation with lipid aldehydes occurs, studies indicate that side chain alkylation is ϳ10-fold more prevalent than direct side chain oxidation (41).…”
Section: Discussionmentioning
confidence: 99%
“…Methods are in development to isolate and analyze such alkylated peptides to determine the site(s) and stoichiometry of carbonylation. Additionally, although both amino acid side chain oxidation and carbonylation with lipid aldehydes occurs, studies indicate that side chain alkylation is ϳ10-fold more prevalent than direct side chain oxidation (41).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation products can diffuse across membranes, allowing the reactive aldehyde-containing lipids to covalently modify proteins localized throughout the cell and relatively far away from the initial site of ROS formation. Recent studies have suggested that protein carbonylation formed from lipid-derived aldehydes is more prevalent than that formed via direct amino acid side chain oxidation (9). The cellular metabolism of lipid peroxidation products and the fates of their protein targets are diagramed in Fig.…”
mentioning
confidence: 99%
“…Indirect protein carbonylation is more prevalent and involves a reaction with oxidized AGE (advanced glycation end) products (described in glycoproteomics, section 3.4), or hydroxyl radical-mediated oxidation of lipids. Lipid-derived aldehydes can form Michael adducts with cysteine, histidine, lysine and arginine, and in some cases can further undergo Schiff base formation with amines of adjacent lysines, producing cross-linked amino acids [120,123,124]. Analysis of the resulting PTM diversity is hindered by their instability because carbonyl groups readily undergo Schiff base formation with proximate lysine residues, even when stored at -80 °C [122].…”
Section: Protein Carbonylationmentioning
confidence: 99%